EMPOWERING ISLAMIC BOARDING SCHOOLS' BUSINESS UNITS: A DIGITAL MARKETING OPTIMIZATION MODEL - bin Lahuri, Setiawan; Aniys Nur Fuadah, Risma; Amalia Zuhroh, Ainun (Universitas Airlangga, 2024)
Introduction: This study aims to develop a comprehensive digital marketing optimization model specifically designed for Islamic boarding schools in East Java, a province with a high concentration of Islamic boarding schools and their associated business units. The intense competition among these schools necessitates the adoption of digital transformation to enhance the effectiveness and competitiveness of their business operations. Methods: Utilizing qualitative methods and the Analytic Network Process (ANP) for data analysis, this study identifies critical internal challenges, such as low product quality, and external threats, including competition from larger enterprises. The research also explores alternative strategies to address these challenges. Results: The findings indicate that the primary barriers to effective digital marketing stem from both internal and external factors. Strategic solutions are proposed, including the implementation of Search Engine Optimization (SEO), social media marketing, and targeted advertising through platforms like Google Ads. Moreover, the study highlights the importance of continuous mentoring and counseling to support the successful application of these strategies. Conclusion and suggestion: This research provides valuable insights into leveraging digital marketing to enhance human resource potential and improve product quality, thereby fostering economic empowerment within Islamic boarding schools and increasing their competitiveness.